Women Empowerment through Participation in Panchayat Raj Institutions : Successful Case Studies from Tamil nadu - V. Stephen and A Relton (KILA Journal of Local Governance, 2013)
This paper analyzes the impact of women’s participation in Panchayat Raj Institutions (PRIs) in Tamil Nadu towards the process of women’s empowerment. The study on the participation of women in local governance plays a pivotal role in the advancement of women. Without the active participation of women and the incorporation of women’s perspective at all levels of decision-making, the goals of equality, development and peace cannot be achieved. The paper examines how change in agents i.e. reservation and participation of women in local governance are raising consciousness of women’s issues and bringing about the changes in the institutional structures and processes influencing the governance discourse in itself.